Arene ruthenium chemistry - Bates, Richard Simon (1990)
This thesis describes the synthesis and reactivity studies of new arene-ruthenium(II) and arene-ruthenium(O) complexes. Ultrasound has been investigated as an alternative energy source, with the overall aim of synthesising arene ruthenium clusters. Chapter 1 gives an introduction and summary of the known arene ruthenium chemistry reported to date. Chapter 2 reports the synthesis of (CGH6)Ru(C2H4)2 and (MeC6H4CHMe2)Ru(C2H4)2. Low temperature protonation studies generated (C6H6)Ru(H)(CZH4)2' and (MeC6H4CHMe2)Ru(H)(C2H4)7ý. These are observed by 1H nmr spectroscopy to undergo two dynamic processes, rotation of the ethylene ligands and an exchange between the hydride and the hydrogens of the ethylenes. On protonation with trifluoroacetic acid (C6H6)Ru(02CCF3)2 has been shown to be the final product. Nucleophilic substitution investigations of the bis(ethylene) complexes has determined that the arene is more labile than the coordinated ethylene. Chapter 3 reports the generation of a reactive intermediate, [(MeC6H4CHMez)Ru(THF)2]", and the reactions it undergoes. The synthesis and stereochemistry of the new complexes [(MeC6H4CHMe2)RuBr(C3H5)] and Ru(H)[(C6H40) (OPh)2][P(OPh)3]3 are reported. Chapter 4 describes the successful synthesis of the project goal, with the formation of the trimer [(MeC. H., CHMe2)3Ru3Se,_1` and the tetra nuclear species [(MeC6H4CHMe2)4Ru4H4]2'. Electrochemistry shows both complexes undergo two, one-electron reversible reductions to generate their neutral analogues. Ru3(CO)12 was formed when arene ruthenium carbonyl clusters were sought. Chapter 5 reports the formation and reactivity of arene ruthenium complexes containing nitrogen based ligands. The half sandwich complexes, (arene)RuCl2(NH2R) (arene = C6H6, R= Et, CMe, C6H4Me; McC6H4CHMe2, R=CMe3) and (C. H6)RuCl(NHZCGH4Me)Z' have been synthesised in good yield. However, these complexes are not synthetically useful as substrates for cluster synthesis, although (C6H6)RuC12(NH2CMe3) can be converted to the mixed ethoxide-halide dimer, [(C6H6)Ru(OEt)]2Cl`. Me3SiN3 on reaction with [(MeC6H4CHMe2)RuC12]2 affords [(MeC6H4CHMe2)RuCl(N3)]Z. An X-ray crystal structure determination of this complex showed the nitrogens bridging the two ruthenium atoms are pyramidal rather than the expected planar in geometry. [(MeC6H4CHMe2)RuCl(N3)]2 undergoes chloride loss to form the triply bridged dimer, [(MeCGH4CHMe2)RuCl(N3)z]', and bridge cleavage to form [(MeC, H4CHMe2)RuCl(N3)PPh3]. The latter complex is believed to undergo disproportionation in solution. Conclusions and future directions of the project are discussed in chapter. 6. The appendix provides a discussion of ultrasound proposed structure.